2019
DOI: 10.31557/apjcp.2019.20.12.3811
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Incidence of Breast Cancer Following the Radiological Accident in Goiânia: A 25-Year Analysis

Abstract: Background:The largest radiological accident to occur in any urban area happened in Goiânia, Brazil, in 1987. One major concern regarding deleterious effects in the population was a possible increase in the breast cancer incidence. This study analyzed trends in the incidence of breast cancer over the 25-year period following the radiological accident. Methods: This ecological, population-based study was conducted to determine the incidence of breast cancer in female residents of Goiânia, Goiás, Brazil, between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…17,18 Nevertheless, population-based studies with almost 30 years of follow-up have also suggested that was no association between the radiological accident and the incidence of cancer in the city. 19,20 One possible explanation for this is that the genetic changes induced in the exposed population were not pathogenic or did not translate into increased cancer risk. 21 In the overall analysis on breast cancer incidence in Goiânia, the peak incidence of the disease would have been expected in 1997, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…17,18 Nevertheless, population-based studies with almost 30 years of follow-up have also suggested that was no association between the radiological accident and the incidence of cancer in the city. 19,20 One possible explanation for this is that the genetic changes induced in the exposed population were not pathogenic or did not translate into increased cancer risk. 21 In the overall analysis on breast cancer incidence in Goiânia, the peak incidence of the disease would have been expected in 1997, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study showed that the increase in the incidence of breast cancer in Goiânia was gradual between 1988 and 2004, with a tendency to stabilize after 2005. 20 In this context, analysis on the incidence associated with the geospatial distribution pattern may identify points of higher concentration of the disease (clusters) and assist in constructing hypotheses about neoplasm behavioral change at that particular location. [22][23][24] For the city of Goiânia, the estimates for 2016 showed that there Considering the total number of new cases of breast cancer identified in this study within the period between 2001 and 2010, the crude incidence rates per 100,000 women were much higher in the study area (102.91 cases per 100,000) than outside the study area (46.86 cases per 100,000), and higher than the average in Goiânia (66.59 cases per 100,000 women).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ingestion of 137 Cs leads to the accumulation of this radioactive isotope in so tissues from the thyroid, lungs, breast, and bone marrow, [11][12][13][14] resulting in a biological action similar to a continuous exposure to radiation from external sources. The ultimate effect of bioaccumulation of 137 Cs in humans, in dependency to the amount ingested, is the development of radiation-induced malignancies, [15][16][17] as well as mutagenesis in germinal cells. 18,19 Many methods are currently available for decontamination of radioactive wastewater from nuclear ssion products.…”
Section: Introductionmentioning
confidence: 99%